Difference in clinical profile between juvenile onset and adult-onset systemic lupus erythematosus: a meta-analysis - Shah, Mandar Kalpesh; Shah, Mihika Ashish; Goghawala, Gayatri Anand; Kathayat, Priyangi Manohar; Shah, Parshwa Keyur; Shah, Sharan Dharmesh; Patel, Harshil Devang; Patel, Kaushal; Abbas, Kiran; Srivastava, Puja; Pandya, Sapan C. (International Journal of Research in Medical Sciences, 2021)
The aim was to systematically review the studies that compared clinical and serological variation between adult-onset systematic lupus erythematosus (aSLE) andjuvenile-onset systematic lupus erythematosus (jSLE). A comprehensive literature search was done, in various available electronic databases for relevant publication that compared juvenile onset SLE and adult onset SLE. The data of adverse clinical features, serological profile and mortality were extracted. Juvenile onset was defined as <18 years and adult onset was defined as >18 years. The methodological quality of study was assessed by Newcastle Ottawa scale (NOS) criteria and R version 3.3.1 was used for analysis and ORs and 95% CIs, were used as statistical parameter. A total of 14,920 patients; (12,230: aSLE, and 2,690: jSLE) were included. Renal involvement especially nephritis was significantly more in j-SLE OR: 2.18, 95% CI: [1.81;2.62]; I2=10.8% whereas musculoskeletal was significant in aSLE O.R: 0.64; C.I: [0.44; 0.93]; I2=83.4%. Seizure and malar rash were significantly higher in J-SLE OR:1.69, CI: [1.31; 2.18]; I2=31.1%,1.43; C.I [1.04; 1.97]; I2=82%, respectively. Raynaud’s phenomenon and pleuritis were significantly higher in adult onset SLE. Anemia and thrombocytopenia were significantly higher in juvenile onset SLE. Anti-ds DNA, anti-histone, and anti-ribosomal-P were more frequent in juvenile-onset SLE while, anti-Ro was more common in adult-onset disease. The cause of mortality was not significantly different in both groups. Renal biopsy of class III and IV combined and class V were significantly more in adult-onset SLE. SLEDAI was higher in j-SLE. Meta-analysis indicated that, regardless of many similar clinical and serological manifestations, there is still some variation between adult-onset SLE and juvenile-onset SLE. Although, SLE disease is continuum from juvenile to adult but disease aggressive in juvenile onset SLE.